IMPLEMENTASI PENDIDIKAN TAUHID PADA ANAK USIA DINI DI TAMAN KANAK-KANAK ISLAM TAHFIDZUL QUR’AN (TKITQ) IMAM SYAFI’I BANJARMASIN - Najemi; Samdani Samdani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Ibnul Qayyim Rahimahullah revealed that teaching children the sentence of monotheism is done when the child begins to interact with the surrounding environment. Since this is when children begin to hear words and see movements, in accordance with the characteristics of early childhood, namely great imitators, it is by seeing and hearing that children will begin to imitate without being ordered. Children should be taught the sentence La ilaha illallah as the first sentence that children can say fluently. Monotheism is the basis for humans in worship, which is why children are taught from an early age about the oneness of Allah, rububiyah, uluhiyah, as well as asthma and the attributes of Allah. The application of monotheism in early childhood can actually be given since the child is still in the womb. This is believed by Zakiah Drajad who said that the basic pattern in implementing monotheism education as a child's character formation can be done by parents when the child is in the womb by inviting them to communicate gently, reading verses from the Koran which can help development. child's brain.